Association of metabolic syndrome and chronic kidney disease with atrial fibrillation: A nationwide population-based study in Korea. (February 2019) - Choe, Won-Seok; Choi, Eue-Keun; Han, Kyung-Do; Lee, Eui-Jae; Lee, So-Ryoung; Cha, Myung-Jin; Oh, Seil
Highlights: Patients with Metabolic syndrome (MetS) and chronic kidney disease (CKD) share a common epidemiological risk profile, and a positive relationship between the prevalence of MetS and CKD was observed. MetS and CKD are both individually significant predictors of the development of AF, and their combination further increases the risk of incident AF. The incidence and prevalence of both MetS and CKD are rapidly growing worldwide, which will significantly affect the development of AF and result in health economic burden. Abstract: Aims: Metabolic syndrome (MetS) and chronic kidney disease (CKD) are significant risk factors for incident atrial fibrillation (AF). Few studies have reported the synergistic effect of MetS and CKD on development of AF. We investigated the individual and synergistic effects of MetS and CKD on the risk of incident AF. Methods: We studied a retrospective cohort comprising 22, 886, 663 Koreans whose data was obtained from the national health claims database established by the Korean National Health Insurance Service between 2008 and 2013. Patients were classified into a MetS and a CKD group and followed-up until 2016 for new-onset AF. A Cox proportional hazards model assessed the independent and synergistic effect of MetS and CKD on the risk of incident AF. Results: The prevalence of MetS and CKD in these patients was 27.4% and 5.4%, respectively. During a mean follow-up of 5.4 years, AF developed in 225, 529 patients (1% of the total cohort). The adjusted hazard ratio (HR) for incident AF was 1.38 (95% confidence interval [CI] 1.36–1.39) for MetS, and 1.35 (95% CI 1.34–1.37) for CKD. Patients with MetS and CKD showed a higher risk of AF (HR 1.75, 95% CI 1.73–1.78) than that observed in those without MetS and CKD. Conclusions: The combination of MetS and CKD showed a high risk of development of AF in a large-scale nationwide cohort. Further studies are warranted to determine whether pharmacological and/or lifestyle interventions can control/manage these modifiable risk factors to reduce the risk of development of AF.